Isolating Tryptophan Regulatory Mutants in Escherichia coli by Using a trp-lac Fusion Strain - Reznikoff, William S. (1972)
A trp-lac fusion strain of Escherichia coli in which the lac structural genes are part of the tryptophan operon has been used to isolate trp regulatory mutants. This was accomplished by isolating lac(+) colonies on either lactose-minimal agar or lactose-MacConkey indicator agar. Seventy-seven of 78 lac(+) isolates contained mutations which mapped near the ara locus and most of these isolates were found to be 5-methyltryptophan-resistant after introduction of an F-trp episome. The lac(+) phenotypes of these 77 isolates were therefore probably the result of trpR(−) mutations. The one remaining isolate carried a mutation which was not part of the trp regulatory system.